OsTZF1, a CCCH-Tandem Zinc Finger Protein, Confers Delayed Senescence and Stress Tolerance in Rice by Regulating Stress-Related Genes(1)([W])([OA]) - Jan, Asad (American Society of Plant Biologists, 2013)
OsTZF1 is a member of the CCCH-type zinc finger gene family in rice (Oryza sativa). Expression of OsTZF1 was induced by drought, high-salt stress, and hydrogen peroxide. OsTZF1 gene expression was also induced by abscisic acid, methyl jasmonate, and salicylic acid. Histochemical activity of β-glucuronidase in transgenic rice plants containing the promoter of OsTZF1 fused with β-glucuronidase was observed in callus, coleoptile, young leaf, and panicle tissues. Upon stress, OsTZF1-green fluorescent protein localization was observed in the cytoplasm and cytoplasmic foci. Transgenic rice plants overexpressing OsTZF1 driven by a maize (Zea mays) ubiquitin promoter (Ubi:OsTZF1-OX [for overexpression]) exhibited delayed seed germination, growth retardation at the seedling stage, and delayed leaf senescence. RNA interference (RNAi) knocked-down plants (OsTZF1-RNAi) showed early seed germination, enhanced seedling growth, and early leaf senescence compared with controls. Ubi:OsTZF1-OX plants showed improved tolerance to high-salt and drought stresses and vice versa for OsTZF1-RNAi plants. Microarray analysis revealed that genes related to stress, reactive oxygen species homeostasis, and metal homeostasis were regulated in the Ubi:OsTZF1-OX plants. RNA-binding assays indicated that OsTZF1 binds to U-rich regions in the 3′ untranslated region of messenger RNAs, suggesting that OsTZF1 might be associated with RNA metabolism of stress-responsive genes. OsTZF1 may serve as a useful biotechnological tool for the improvement of stress tolerance in various plants through the control of RNA metabolism of stress-responsive genes.